The developing world in The New England Journal of Medicine - Banerjee Amitava; Lown Bernard (BMC, 2006)
Abstract Background Rampant disease in poor countries impedes development and contributes to growing North-South disparities; however, leading international medical journals underreport on health research priorities for developing countries. Methods We examined 416 weekly issues of the New England Journal of Medicine (NEJM) over an eight-year period, January 1997 to December 2004. A total of 8857 articles were reviewed by both authors. The content of each issue was evaluated in six categories: research, review articles, editorial, correspondence, book reviews and miscellaneous. If the title or abstract concerned a topic pertinent to any health issue in the developing world, the article was reviewed. Results Over the eight years covered in this study, 1997-2004, in the three essential categories of original research articles, review articles and editorials, less than 3.0 percent of these addressed health issues in the developing world. Publications relevant to DC were largely concerned with HIV and communicable diseases and constituted 135 of the 202 articles of which 63 were devoted to HIV. Only 23 articles addressed non-communicable disease in the DC and only a single article - a book review - discussed heart disease. Conclusion The medical information gap between rich and poor countries as judged by publications in the NEJM appears to be larger than the gap in the funding for research. Under-representation of developing world health issues in the medical literature is a global phenomenon. International medical journals cannot rectify global inequities, but they have an important role in educating their constituencies about the global divide.